The Degree of Proficiency of the Students of the Physics Branch in the College of Basic Education for the Electronic Exam Using the Edmodo Platform and their Tendencies Towards it - Rasha Abdul-Hussein Sahib Abdul-Hassan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Among the objectives of this paper is to identify the degree of proficiency of the students of the Physics Branch at the College of Basic Education for the electronic exam using a platform and their preferences for it, and in order to achieve the two goals of the Edmodo paper, which includes, and in order to achieve the two goals of the paper, the papers adopted the descriptive analytical approach, and the paper community consisted of (613) students from the students of the Department of Science In its two branches (Biology and Physics) in the College of Basic Education at the University of Maysan, the paper sample amounted to (170) male and female students from the students of the physics branch in its stages (second, third and fourth), where they were chosen in an intentional way, and by reviewing the literature and studies Previously, the two paperes prepared two paper tools, and the first tool for paper was (the electronic exam using the Edmodo platform) and it consisted of (40) paragraphs, and the second tool for the paper was represented by the (the propensity scale towards the electronic exam using the Edmodo platform), which consisted of ( 45) Paragraph, and the validity and reliability of the two tools were verified and applied to the selected sample. The results showed a statistically significant difference in the students’ responses about the degree of their proficiency in the electronic exam using the Edmodo platform. This result is due to the availability of Sufficient experience and skill of some members of the paper sample from the students of the physics branch with modern electronic devices and means of communication, as well as the presence of a statistically significant difference in the students’ responses about their tendencies towards the electronic exam using the Edmodo platform. Modern technology among some members of the paper sample from the students of the physics branch to deal with modern electronic devices and means.